Research of the Finite Element Simulation Method of Multi-tooth Meshing Gear Train Under Complex Mechanical Behavior - Jianfang Xia; Qicheng He; Dongyang Liu; Fangjun Gao (Jixie chuandong)
The core transmission unit of the star gear drive reducer is a small-tooth-difference multi-tooth meshing gear train， which involves gears with multi-tooth elastic contact meshing， shaft-hole contact， and crankshaft rotation and so on drive relationship， gear motion includes fixed-axis rotation and compound rotation （rotation and translation）.The relationship between mechanics and kinematics is more complicated， and there is no relevant theory in the calculation of strength， deformation and so on. In order to obtain the gear contact strength and bending strength， based on the mechanical theory and computational mechanics simulation methods， under the premise of meeting the requirements of engineering calculation accuracy， a simplified method of the finite element physical model under the complex mechanical behavior of a multi-tooth meshing gear train is explored， and how to deal with simulation problems such as simplification of crankshafts and bearings， meshing of gear teeth， contact convergence， etc. The simulation process is demonstrated by an example. The result shows that， the star gear drive case has the phenomenon of multi-tooth contact elastic meshing， and the number of contact tooth pairs is in line with expectations. The contact stress of the tooth surface and the bending stress of the tooth root are calculated by simulation and can meet the design requirements， it shows that the correctness of the simulation method. Its simulation technology has important guiding significance for the strength calculation and improved design of star gear drive.